Gravitational Radiation from Keplerian Binary with Oscillating Orbital Plane - Faruque, Syed Badiuzzaman; Nawaz, Muhammad Ali; Ahsan, Muhammad Habibul (Journal of Scientific Research, 2008)
The gravitational radiation from two point masses in Keplerian circular or elliptic orbit is calculated with the assumption that the orbital plane of the binary undergoes small oscillation about the equilibrium x-y plane. This problem is simplification of a physically possible orbit where one of the point masses is spinning whereby the spin-orbit force drives the orbital plane to wobble in a complicated manner. It is shown that the total energy of gravitational radiation emitted by the binary in this case is greater than the energy emitted when the binary orbit is fixed in the x-y plane. The results presented are in fact a generalization of the classic results of Landau and Lifshitz. Keywords: Gravitational wave; Energy; Binary; Oscillating orbit. ©2009 JSR Publications. ISSN: 2070-0237(Print); 2070-0245 (Online). All rights reserved.